468 Racial disparities in patients with covid-19 infection and gynecologic malignancy. (4th December 2020) - Lara, Olivia; Smith, Maria; Wang, Yuyan; O'cearbhaill, Roisin; Blank, Stephanie; Knisely, Anne; Mceachron, Jennifer; Gabor, Lisa; Chapman-Davis, Eloise; Jee, Justin; Isani, Sara; Liu, Mengling; et al.
Abstract : Introduction/Background: Mounting evidence suggests disproportionate COVID-19 hospitalizations and deaths due to racial disparities. The association of race in a cohort of gynecologic oncology patients with SARS-CoV-2 infection is unknown. Methodology: Data were abstracted from gynecologic oncology patients with COVID-19 infection among 8 New York City (NYC) area hospital systems. Multivariable mixed-effects logistic regression model accounting for county clustering was utilized to analyse COVID-19 related hospitalization and mortality. Results: Of 193 patients with gynecologic cancer and COVID-19, 67 (34.7%) were Black and 126 (65.3%) were non-Black. Black patients were more likely to require hospitalization compared with non-Black patients (71.6% [48/67] vs. 46.0% [58/126], P=.001). Of 34 (17.6%) patients who died from COVID-19, 14 (41.2%) were Black. Among those hospitalized, Black patients compared to non-Black patients were more likely to: have ≥ 3 comorbidities (81.1% [30/37] vs 59.2% [29/49], P=.05); reside in Brooklyn (81.0% [17/21] vs 44.4% [12/27], P=.02); live with family (69.4% [25/36] vs 41.6% [37/89], P=.009); and have public insurance (79.6% [39/49] vs 53.4% [39/73], P=.006). In multivariable analysis, for patients younger than 65 years of age, Black patients were more likely to require hospitalization compared to non-Black patients (OR, 4.87; 95% CI 1.82 to 12.99, P=.002). Conclusion: Although Black patients with gynecologic cancer represented only 1/3 of patients, they accounted for disproportionate rates of hospitalization (>45%) and death (>40%) due to COVID-19 infection; younger Black patients had nearly 5-fold greater risk of hospitalization. Efforts to understand and improve these disparities in COVID-19 outcomes in Black patients are critical. Disclosures: B.P. reports grants, personal fees and non-financial support outside the submitted work; institutional PI for industry sponsored trials from Tesaro/GSK, AstraZeneca, Merck, Genentech/Roche, and Clovis Oncology. Compensated advisory boards include Tesaro/GSK, AstraZeneca, Merck and Eisai. J.J. reports a patent license from MDSeq Inc. R.OC reports personal fees from Tesaro, GlaxoSmithKline, Regeneron and Genentech USA, outside the submitted work and non-compensated steering committee member for the PRIMA, Moonstone (Tesaro/GSK) and DUO-O (AstraZeneca) studies. R.OC's institute receives funding for clinical research from Celgene/Juno, Tesaro/GSK, Ludwig Cancer Institute, Abbvie, Regeneron, TCR2 Therapeutics, Atara Biotherapeutics, Marker Therapeutics, Syndax Pharmaceuticals, Genmab Therapeutics, Sellas Therapeutics, Genentech, Kite Pharma, Gynecologic Oncology Foundation. S.V.B. has research collaborations with Roche/Genentech, Tesaro/GK, Seattle Genetics, Merck and Asta Zeneca